The Characterization of Obsidian and its Application to the Mediterranean Region - Cann, J. R. (1964)
for 1964; Near Eastern sources of obsidian (cf. fig. 7): Çukurkent, Çatal Hüyük, Mersin, Chagar Pazar, Arpachiya, Lake Van, Yanik Tepe, Armenia.